Penaksiran Endapan Timah Primer Menggunakan Metode Resistivitas dan Metode Geomagnetik Di Bukit Sambunggiri Kecamatan Merawang Kabupaten Bangka - Mardiah Mardiah; Guskarnali Guskarnali (PROMINE, 2019)
Cassitterit is a valuable mineral containing tin and other minerals as mining products in the Bangka Belitung Islands region. Sambung giri Hill, Merawang District, Bangka Regency is one of the places where primary tin deposits occur. Estimation of subsurface images can be interpreted using geophysical methods in the form of resistivity methods and geomagnetic methods. The measurement of resistivity method uses 6 lines with dipole-dipole configuration while the geomagnetic method with looping measurement technique as many as 13 lines with each line consists of several measurement points within 20 meters, consisting of 10 lines to the South-North direction, and 3 trajectories to the West- East. Based on the results of the study, the primary tin deposit estimation from the resistivity method in the form of a cross section of resistivity shows a low resistivity value (<700 Ohm.m) while the geomagentic method in the form of Reduction To Equator (RTE) shows a low geomagnetic anomaly (<0.8 nT). The spread of primary tin deposits is estimated to be found in the Northwest-Southeast direction.